PRTFDC1 Is a Genetic Modifier of HPRT-Deficiency in the Mouse - Keebaugh, Alaine C. (Public Library of Science, 2011)
Lesch-Nyhan disease (LND) is a severe X-linked neurological disorder caused by a deficiency of hypoxanthine phosphoribosyltransferase (HPRT). In contrast, HPRT-deficiency in the mouse does not result in the profound phenotypes such as self-injurious behavior observed in humans, and the genetic basis for this phenotypic disparity between HPRT-deficient humans and mice is unknown. To test the hypothesis that HPRT deficiency is modified by the presence/absence of phosphoribosyltransferase domain containing 1 (PRTFDC1), a paralog of HPRT that is a functional gene in humans but an inactivated pseudogene in mice, we created transgenic mice that express human PRTFDC1 in wild-type and HPRT-deficient backgrounds. Male mice expressing PRTFDC1 on either genetic background were viable and fertile. However, the presence of PRTFDC1 in the HPRT-deficient, but not wild-type mice, increased aggression as well as sensitivity to a specific amphetamine-induced stereotypy, both of which are reminiscent of the increased aggressive and self-injurious behavior exhibited by patients with LND. These results demonstrate that PRTFDC1 is a genetic modifier of HPRT-deficiency in the mouse and could therefore have important implications for unraveling the molecular etiology of LND.